2009
DOI: 10.2164/jandrol.108.005934
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in the Testes of Different Murine Strains Under Normal and Hyperthermic Conditions

Abstract: Cryptorchidism and scrotal heating result in abnormal spermatogenesis, but the mechanism(s) prescribing this temperature sensitivity are unknown. It was previously reported that the AKR/N or MRL/MpJ-+/+ mouse testis is more heat-resistant than the testis from the C57BL/6 strain. We have attempted to probe into the mechanism(s) involved in heat sensitivity by examining global gene expression profiles of normal and heat-treated testes from C57BL/6, AKR/N, and MRL/MpJ-+/+ mice by microarray analysis. In the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 70 publications
(71 reference statements)
1
25
0
Order By: Relevance
“…For mice of the MRL/Mpj strain, large numbers of germ cells remained in the cryptorchid testis and the reduction in size compared to the control testis was only 31 per cent (figure 8) (Kon & Endoh 2001). Similarly, scrotal heating of 438C induced germ cell apoptosis and loss in both C57BL/6 and AKR/N males but the magnitude of the effects was greater for C57BL/6 (Li et al 2009). The resistance of germ cells of MRL/Mpj mice to elevated testicular temperature may be caused by a mutation in exonuclease-1 (Namiki et al 2003).…”
Section: Genetic Plasticity Controlling the Magnitude Of Heat Stress mentioning
confidence: 97%
“…For mice of the MRL/Mpj strain, large numbers of germ cells remained in the cryptorchid testis and the reduction in size compared to the control testis was only 31 per cent (figure 8) (Kon & Endoh 2001). Similarly, scrotal heating of 438C induced germ cell apoptosis and loss in both C57BL/6 and AKR/N males but the magnitude of the effects was greater for C57BL/6 (Li et al 2009). The resistance of germ cells of MRL/Mpj mice to elevated testicular temperature may be caused by a mutation in exonuclease-1 (Namiki et al 2003).…”
Section: Genetic Plasticity Controlling the Magnitude Of Heat Stress mentioning
confidence: 97%
“…Indeed, the scrotal temperature is 2-8°C lower than the rest of the body. Experimental hyperthermia has been shown to cause similar degenerative changes as induced by cryptorchidism ( 45 ) . It has been suggested that selective signaling pathways deregulated in different testicular cell populations might be responsible for spermatogenesis arrest ( 46 ) .…”
Section: Two Phases Of Testicular Descentmentioning
confidence: 92%
“…Recently, a number of whole-genome gene expression studies have been performed on cryptorchid testes of rodent models with induced and hereditary cryptorchidism, as well as in cryptorchid human testes ( 14,45,46,54,(85)(86)(87) . Additionally, the gene expression profi les of rodent and primate testes under hyperthermic conditions have been analyzed ( 45,49 ) .…”
Section: Somatic Cell Function In Cryptorchid Testismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, an earlier study on gene regulation after SHS induction in AKR/N mice, whose spermatocytes are also relatively resistant to heat stress, suggested that both somatic cells and germ cells contribute to the heat resistance of AKR/N testes during the early response to hyperthermia. 37 Thus, contributions from spermatocytes and Sertoli cells, such as the maintenance of BTB integrity, might be necessary for heat shockeresistant spermatogenesis in MRL mice.…”
Section: Heat Shockeresistant Spermatogenesis In Mrl Micementioning
confidence: 99%